KEKERASAN DALAM PACARAN (KDP) PADA REMAJA PUTRI USIA 15-18 TAHUN DI SMA MUHAMMADIYAH 4 KOTA BENGKULU - Sembiring, Gaipyana (JURNAL MEDIA KESEHATAN, 2014)
Many teens do not realize that behind the beauty of dating did not escape from the things that lead to violence is popularly called dating violence. This event looks like the iceberg phenomenon, where the case is still far greater, but many things that make it rise to the surface. The purpose of this study is to describe dating violence in adolescent girls aged 15-18 years. The study uses a descriptive research design. The results showed that 56.3 % experienced emotional abuse in dating, 23.4% experienced sexual violence in dating, 39.2 % experienced physical violence in dating, 29.7% experienced economic abuse in dating and 43 % had a tendency to be a victim violence in dating. Sexual violence is a form of violence experienced by most tendency to violence in dating (30%). The conclusion of this study is the high incidence of dating violence in adolescent girls aged 15-18 years.